High-temperature PEM fuel cell electrode catalyst layers part 1: Microstructure reconstructed using FIB-SEM tomography and its calculated effective transport properties. (1st May 2022) - Prokop, M.; Vesely, M.; Capek, P.; Paidar, M.; Bouzek, K.
Highlights: FIB-SEM tomography on catalyst layer (CL) bonded with polybenzimidazole is feasible. Polybenzimidazole-bonded CL has homogenous Pt distribution but cracked structure. In polybenzimidazole-bonded CL Pt penetrates into the microporous layer. Heat treatment of CL improves its electric conductivity but decreases permeability. Abstract: The main topic of this study is the microstructure of catalyst layers (CLs) of a high-temperature gas diffusion electrode in a PEM fuel cell, bonded by polybenzimidazole. Using focused ion beam scanning electron microscopy in both the secondary and backscattered electron modes, Pt distribution in the CLs was studied. It was found that the choice of binder and preparation history had an important impact on the CL 3D microstructures. Polybenzimidazole-bonded CLs exhibited smooth surface, low porosity and homogeneous distribution of Pt. On the other hand, penetration of Pt into the microporous layer of the electrode was observed. Good thermal and mechanical stability of the CL made it possible to carry out FIB-SEM tomography and to reproduce its 3D microstructure by alternating use of ion milling and imaging of emerging cross-sectional planes. The 3D microstructure obtained served as an input for mathematical models allowing an evaluation of the effective macroscopic transport properties of the CL. This represents important information for reliable mathematical modelling and optimisation of the high-temperature PEM fuel cell. Graphical abstract: Image, graphical abstract